The Thoracic Surgery Residents Association: Past contributions, current efforts, and future directions - Brescia, Alexander A. (J Thorac Cardiovasc Surg, 2021)
OBJECTIVE: The Thoracic Surgery Residents Association (TSRA) is a resident-led organization established in 1997 under the guidance of the Thoracic Surgery Directors Association to represent the interests and educational needs of cardiothoracic surgery residents. We aim to describe the past contributions, current efforts, and future directions of the TSRA within a conceptual framework of the TSRA mission. METHODS: Primary review of educational resources was performed to report goals and content of past contributions. TSRA Executive Committee input was used to describe current resources and activities, as well as the future goals of the TSRA. Podcast analytics were performed to report national and global usage. RESULTS: Since 2011, the TSRA has published 3 review textbooks, 5 reference guides, 3 test-preparation textbooks, 1 supplementary publication, and 1 multiple-choice question bank and mobile application, all written and developed by cardiothoracic surgery trainees. In total 108 podcasts have been recorded by mentored trainees, with more than 175,000 unique listens. Most recently, the TSRA has begun facilitating trainee submissions to Young Surgeon's Notes, fostered a trainee mentorship program, developed the monthly TSRA Newsletter, and established a wide-reaching presence on Facebook, Twitter, and Instagram to help disseminate educational resources and opportunities for trainees. CONCLUSIONS: The TSRA continues to be the leading cardiothoracic surgery resident organization in North America, providing educational resources and networking opportunities for all trainees. Future directions include development of an integrated disease-based resource and continued collaboration within and beyond our specialty to enhance the educational opportunities and career development of cardiothoracic trainees.